On the psychology of vague predicates - Bonini, N; Osherson, D; Viale, R; Williamson, T (Blackwell Publishers Ltd., 1999)
Most speakers experience unclarity about the application of predicates like tall and red to liminal cases. We formulate alternative psychological hypotheses about the nature of this unclarity, and report experiments that provide a partial test of them. A psychologized version of the 'vagueness-as-ignorance' theory is then advanced and defended.